PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTUAN MEDIA PAREHAN DAN QUIZIZZ DALAM MATERI PENJUMLAHAN DAN PENGURANGAN BILANGAN PADA SISWA KELAS IV SD - Adaninggar Prameswari; Panca Dewi Purwati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Conventional learning methods should be replaced with learning approaches that are in accordance with the 21st century learning era. The application of the recommended learning model for mathematics learning in this study is the problem-based leaning learning model assisted by Parehan and quizizz media. The purpose of the study was to (1) describe the application of the problem based learning model assisted by Parehan and quizizz media in addition and subtraction material in grade IV students of SDN 2 Trucuk, and (2) describe the learning outcomes of addition and subtraction material in grade IV students of SDN 2 Trucuk through a problem based learning model assisted by Parehan and quizizz media. This research was conducted at SDN 2 Trucuk with the subject of 15 grade IV students using qualitative descriptive methods to describe the findings. Observations, tests and documentation are used by researchers to retrieve data. The application of the Parehan and quizizz media-assisted problem-based learning model in grade IV of SDN 2 Trucuk went well, It is shown by the increase in student learning outcomes from 6 (40%) students to 14 (93%) students who have scores above KKTP while the remaining only 7% of students whose scores are still below KKTP, however there needs to be a habit of using digital platforms.